2006
DOI: 10.1038/nphys314
|View full text |Cite
|
Sign up to set email alerts
|

Critical phenomena in atmospheric precipitation

Abstract: Critical phenomena near continuous phase transitions are typically observed on the scale of wavelengths of visible light[1]. Here we report similar phenomena for atmospheric precipitation on scales of tens of kilometers. Our observations have important implications not only for meteorology but also for the interpretation of self-organized criticality (SOC) in terms of absorbing-state phase transitions, where feedback mechanisms between order- and tuning-parameter lead to criticality.[2] While numerically the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
358
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(395 citation statements)
references
References 29 publications
32
358
0
5
Order By: Relevance
“…Figure 4a shows precipitation and entraining CAPE conditionally averaged on w for the ARM data (C. E. Holloway & J. D. Neelin 2008, unpublished manuscript). The sharp pickup of precipitation at a high enough value of w agrees with satellite analyses in Bretherton et al (2004) and Peters & Neelin (2006). The entraining CAPE (Brown & Zhang 1997), taken for the positively buoyant part of the path of lifted 1000 hPa parcels entraining 0.1% of environmental air per hPa (so that the virtual T c from §1c includes mixing with T ), also shows a sharp pickup, which appears to be due to both the moister free troposphere and the slightly higher ABL moist static energy associated with larger w. The CIN is always below 6 J kg K1 for these composite profiles, and there is no obvious relationship between CIN and the precipitation pickup.…”
Section: Vertical Structure Associated With Qesupporting
confidence: 79%
See 2 more Smart Citations
“…Figure 4a shows precipitation and entraining CAPE conditionally averaged on w for the ARM data (C. E. Holloway & J. D. Neelin 2008, unpublished manuscript). The sharp pickup of precipitation at a high enough value of w agrees with satellite analyses in Bretherton et al (2004) and Peters & Neelin (2006). The entraining CAPE (Brown & Zhang 1997), taken for the positively buoyant part of the path of lifted 1000 hPa parcels entraining 0.1% of environmental air per hPa (so that the virtual T c from §1c includes mixing with T ), also shows a sharp pickup, which appears to be due to both the moister free troposphere and the slightly higher ABL moist static energy associated with larger w. The CIN is always below 6 J kg K1 for these composite profiles, and there is no obvious relationship between CIN and the precipitation pickup.…”
Section: Vertical Structure Associated With Qesupporting
confidence: 79%
“…The exponent b, on the other hand, is predicted to be robust. This was confirmed observationally: b is comparatively invariant under changes of ocean basin (Peters & Neelin 2006) or temperature. While critical values, w c (T ), and amplitudes a(T ) needed to be adjusted for each value of (vertically averaged) tropospheric temperature in figure 5a, no changes were made to b. Rescaling the water vapour axis with w c (T ) and the precipitation axis with a(T ), the curves collapse (figure 6a).…”
Section: Characteristics Of the Transition To Strong Convectionsupporting
confidence: 59%
See 1 more Smart Citation
“…Many studies have found a strong relationship between tropospheric water vapour and precipitation in observations (Bretherton et al, 2004;Peters and Neelin, 2006;Holloway and Neelin, 2009) and CSRMs (Grabowski, 2003;Derbyshire et al, 2004;Bretherton et al, 2005). However, parametrized convection usually lacks this strong relationship; in particular, models with parametrized convection tend to have too much light rain falling in relatively dry tropospheric conditions (Thayer-Calder and Randall, 2009, their figure 4).…”
Section: Environmental Conditions By Rain Ratementioning
confidence: 99%
“…[53] The sharp transition in NGMS for the precipitating versus nonprecipitating equilibrium states could be related to the Peters and Neelin [2006] [see also Neelin et al, 2009] hypothesis that the tropical atmosphere represents an observable example of self-organized criticality. Though further work is necessary to verify this in the context of our CRM, the current work suggests that NGMS could be an important parameter for understanding this phenomenon.…”
Section: Ngms In Steady Statementioning
confidence: 99%